Dynamics of the surface layer diurnal cycle in the equatorial Atlantic Ocean (0°, 23°W). Issue 1 (30th January 2015) - Wenegrat, Jacob O.; McPhaden, Michael J.
Abstract A 15 year time series (1999–2014) from the 0°, 23°W Prediction and Research Moored Array in the Tropical Atlantic (PIRATA) mooring, which includes an 8 month record (October 2008 to June 2009) of high‐resolution near‐surface velocity data, is used to analyze the diurnal variability of sea surface temperature, shear, and stratification in the central equatorial Atlantic. The ocean diurnal cycle exhibits pronounced seasonality that is linked to seasonal variations in the surface wind field. In boreal summer and fall, steady trade winds and clear skies dominate, with limited diurnal variability in sea surface temperature. Diurnal shear layers, with reduced Richardson numbers, are regularly observed descending into the marginally unstable equatorial undercurrent below the mixed layer, conditions favorable for the generation of deep‐cycle turbulence. In contrast, in boreal winter and spring, winds are lighter and more variable, mixed layers are shallow, and diurnal variability of sea surface temperature is large. During these conditions, diurnal shear layers are less prominent, and the stability of the undercurrent increases, suggesting seasonal covariance between diurnal near‐surface shear and deep‐cycle turbulence. Modulation of the ocean diurnal cycle by tropical instability waves is also identified. This work provides the first observational assessment of the diurnal cycle of near‐surface shear, stratification, and marginal instability in the equatorial Atlantic, confirming previous modeling results and offering a complementary perspective on similar work in the equatorial Pacific.